Acute kidney injury as a risk factor for atrial fibrillation after coronary artery bypass grafting — effects of sodium-glucose cotransporter-2 inhibitors - L. V. Kremneva; L. A. Arutyunyan; L. I. Gapon; S. N. Suplotov; S. V. Shalaev (Рациональная фармакотерапия в кардиологии)
Aim. To identify predictors of paroxysmal atrial fibrillation (pAF) in patients with stable angina after coronary artery bypass grafting (CABG), as well as to evaluate the effect of sodium-glucose cotransporter 2 (SGLT-2) inhibitors.Material and methods. We examined 92 patients with stable angina who received CABG, aged 64±7 years (men, 78,3%). Among this cohort, 81,5% of patients had multivessel coronary artery disease, carbohydrate metabolism disorders — 35,6%, hypertension — 96,7%, chronic kidney disease (CKD) — 23,9%, preprocedural pAF — 10,9%, previous myocardial infarction (MI) — 54,3%. Off-pump CABG was performed in 31,5%, including bilateral inthernal thoracic artery grafting — in 50%. Cardiopulmonary bypass time was 68 (55-83) minutes. The number of grafts was 2,7±0,7. In addition, 18,5% of individuals received SGLT-2 inhibitors. Serum creatinine content was determined by the Jaffe method, and CKD was diagnosed with glomerular filtration rate <60 ml/min. Acute kidney injury (AKI) was assessed according to the KDIGO criteria (2012).Results. The number of patients who had pAF after CABG was 29,3%, AKI — 16,3%. There were following parameters associated with pAF after CABG: creatinine (100;82-142 in patients with pAF and 83;69-105 μmol/l — without pAF, p=0,032) and urea (7,8;5,8-9,7 in patients with pAF and 5,9;4,7-9,1 mmol/l — without pAF, p=0,025) one day after the intervention; postoperative AKI was revealed in 33,3% and 9,2% (p=0,004), while the number of patients taking SGLT-2 inhibitors was 3,7% and 24,6% (p=0,019) in those with and without pAF, respectively. The probability of pAF after CABG increased by an average of 5,5 times with AKI. Patients with pAF after CABG compared to patients without pAF have a higher rate of AKI, intraoperative MI, and cardiac death.Conclusion. The number of patients with pAF after CABG was 29,3%, AKI — 16,3%. Post-CABG pAF predictor was postoperative AKI. The use of SGLT-2 inhibitors was associated with a lower incidence of pAF after intervention. Patients with pAF after CABG have a poor inhospital prognosis.